Genetic diversity of two Daphnia-infecting microsporidian parasites, based on sequence variation in the internal transcribed spacer region - González-Tortuero, Enrique; Rusek, Jakub; Maayan, Inbar; Petrusek, Adam; Piálek, Lubomír; Laurent, Stefan; Wolinska, Justyna (Parasites & vectors, 2016)
BACKGROUND: Microsporidia are spore-forming obligate intracellular parasites that include both emerging pathogens and economically important disease agents. However, little is known about the genetic diversity of microsporidia. Here, we investigated patterns of geographic population structure, intraspecific genetic variation, and recombination in two microsporidian taxa that commonly infect cladocerans of the Daphnia longispina complex in central Europe. Taken together, this information helps elucidate the reproductive mode and life-cycles of these parasite species. METHODS: Microsporidia-infected Daphnia were sampled from seven drinking water reservoirs in the Czech Republic. Two microsporidia species (Berwaldia schaefernai and microsporidium lineage MIC1) were sequenced at the internal transcribed spacer (ITS) region, using the 454 pyrosequencing platform. Geographical structure analyses were performed applying Fisher's exact tests, analyses of molecular variance, and permutational MANOVA. To evaluate the genetic diversity of the ITS region, the number of polymorphic sites and Tajima's and Watterson's estimators of theta were calculated. Tajima's D was also used to determine if the ITS in these taxa evolved neutrally. Finally, neighbour similarity score and pairwise homology index tests were performed to detect recombination events. RESULTS: While there was little variation among Berwaldia parasite strains infecting different host populations, the among-population genetic variation of MIC1 was significant. Likewise, ITS genetic diversity was lower in Berwaldia than in MIC1. Recombination signals were detected only in Berwaldia. CONCLUSION: Genetic tests showed that parasite populations could have expanded recently after a bottleneck or that the ITS could be under negative selection in both microsporidia species. Recombination analyses might indicate cryptic sex in Berwaldia and pure asexuality in MIC1. The differences observed between the two microsporidian species present an exciting opportunity to study the genetic basis of microsporidia-Daphnia coevolution in natural populations, and to better understand reproduction in these parasites.
Keywords: Cryptic sex; fylogeografie; rekombinace genetická; metagenomika; Daphnia; Phylogeography; Recombination, Genetic; DNA, Intergenic; Česká republika; Haplotypes; genetická variace; Czech Republic; Genetic diversity; Genetic Variation; Microsporidia; zvířata; intergenová DNA; Recombination; Internal transcribed spacer; haplotypy; Metagenomics; Animals